Dynamic ultrasound in evaluating the spectrum of anterior abdominal wall lesions - Rana, Priyanka; D’Souza, John; Joshi, Priscilla; Bandgar, Amol; Mahajan, Mangal; Kulthe, Nikhil (International Surgery Journal, 2019)
Background: Lesions in anterior abdominal wall are evident early and their clinical detection is easy. Ultrasonography is the first investigation for the patient clinically suspected to have an anterior abdominal wall lesion. This study evaluated the anterior abdominal wall pathologies using Dynamic ultrasound (USG) and compared the findings with surgical operative findings. Methods: There were 100 consecutive patients of all age groups with clinically suspected anterior abdominal wall pathologies referred for USG of the abdomen were selected for this study. Results: Our study showed a higher incidence of anterior abdominal wall pathologies in male patients (77 %) with an incidence of 41 % in the age group of >60 years. Hernias had an incidence of 93 % followed by undescended testis: 4 %, Divarication of recti: 2% and Rectus sheath hematoma: 1%. Inguinal hernia was the most common hernia with an incidence of 58%. The findings correlated with surgery and gave a sensitivity of 100 %. Conclusions: Ultrasonography including Dynamic USG is a safe, quick, cost-effective, accurate and non-invasive modality for assessing the anterior abdominal wall lesions with a high sensitivity. Dynamic USG also helped to accurately measure the diameter of the neck and content of the sac which aided the surgeon in managing the repair of the hernia.